(untitled) (Zoological Records and Reviews, 2022)
Insect pollinators provide essential ecosystem services underpinning global food security, yet agricultural intensification has driven severe declines in pollinator diversity and abundance across Europe and beyond. Accurate taxonomic assessment of pollinator communities in agricultural landscapes is fundamental to understanding the drivers of pollinator decline and designing effective conservation interventions, yet many agri-environment monitoring programmes rely on coarse functional group classifications rather than species-level identification. This study presents a comprehensive taxonomic assessment of insect pollinators across three agricultural landscape types – intensive arable, mixed farming, and organic arable – in southwestern France, northeastern Spain, and southern Sweden, using standardised pan-trap and transect survey methods over two growing seasons (2019-2020). A total of 312 pollinator species from 7 orders and 42 families were documented, comprising 148 bee species (Hymenoptera: Apoidea), 84 hoverfly species (Diptera: Syrphidae), 46 butterfly species (Lepidoptera: Papilionoidea), and 34 species from other pollinator groups. Species richness was 47.3% higher in organic compared to intensive arable landscapes (p < 0.001). Floral resource diversity, semi-natural habitat cover, and pesticide application frequency were identified as the strongest predictors of pollinator species richness. Rare and specialist pollinator species were disproportionately associated with field margins containing diverse native wildflower communities. Agri-environment scheme effectiveness varied substantially by pollinator taxonomic group, with hoverflies and solitary bees showing the greatest response to wildflower margin interventions.